Efficiency Optimization of Variable Iron Loss Resistance Asynchronous Motor Based on Grey Wolf Optimization Algorithm - Guo, Zhen; Tong, Di; Zhao, Yan-cheng; Chen, Shuang; Nai, Ji-qiu; Ye, Ming-hao (Journal of electrical engineering & technology, 2024)
Asynchronous motor is widely used in various industrial fields. When asynchronous motor works in case close to the rated load, it will run at maximum efficiency. However, most of the load is 50–100% of rated load and it will lead to the serious waste of energy. This paper proposes an efficiency optimization control strategy based on the grey wolf optimization algorithm to improve the operating efficiency of asynchronous motors at light loads. The motor loss model considering the change of iron loss is established and it makes the asynchronous motor model more accurate. The grey wolf optimization algorithm is used to find the optimized flux value. When the asynchronous motor operates at the optimal flux, the loss power of the motor is decreased and the operation efficiency improves effectively. The proposed method reduces the flux search time and improves the stability of the system. The simulation model is established and the simulation results are provided to verify the feasibility of the proposed control strategy achieving the global efficiency optimum of asynchronous motor.